The Nexus of Service Quality, Customer Experience, and Customer Commitment: The Neglected Mediating Role of Corporate Image - Yingfei, Yang; Mengze, Zhang; Ki-Hyung, Bae (Frontiers in Psychology, 2022)
Quality of service is a major determinant in customer commitment to the organization. Therefore, it is important to understand the importance of service quality for corporate image as well. In this study, the predicting roles of quality of service and customer experience have been unveiled in customer commitment through the mediating effect of corporate image. The population frame used in this study is the customers of logistic services providers in China. A total data from the 366 customers have been used to analyze the hypotheses formulated. The sample has been selected using the convenience sampling and the software used for data analysis is Smart PLS. The analytical technique used is partial least square structural equation modeling. Results of the study show that service quality and customer experience have a significant role in the customer commitment to the suppliers. In addition, it has also been found that service quality and customer experience have a major contribution in building the corporate image of the services suppliers. Further, corporate image played a significant mediating role in the relationship of service quality and customer commitment. The study has theoretically contributed to the body of literature by finding how important is the service quality for predicting customer commitment to the suppliers.